Performances of asphalt mastic incorporating with a home-made sustained-releasing salt storage additive - Wei Du; Qing-liang Wang; Yong-xu Li; Xiao-ning Wang; Xiao-cun Liu; Ya-fei Wang; Yan-min Wang; Jin Li (Case Studies in Construction Materials)
The absence of intrinsic deicing capabilities in conventional asphalt mastic poses a critical challenge in cold-climate regions, where the accumulation of snow and ice can result in hazardous traffic conditions. This research introduces the synthesis and integration of a proprietary salt-storage additive, designated DN-PF, into asphalt mastic for the development of self-deicing pavements. The DN-PF additive comprises a sodium chloride (NaCl) core, supported by diatomite and encapsulated in a phenolic resin matrix, engineered to confer self-deicing functionality to asphalt mastic. The DN-PF asphalt mastic was prepared by substituting all filler with equivalent-volume of DN-PF. A comprehensive assessment of the asphalt mastic properties were investigated via penetration, ductility, softening point, the dynamic shear rheometer (DSR) and Bending Beam Rheometer (BBR) tests. The sustained-releasing efficacy of the DN-PF asphalt mastic was also examined by conductivity test. The results indicated that the inclusion of DN-PF improves the high temperature stability and shear resistance of the DN-PF asphalt mastic. However, it also decreases the plasticity and low-temperature anti-cracking property of the mastic. The dissolution amount of snowmelt salt remained stable with uniform dissolution speed, highlighting enhanced sustained-release properties of additives. However, in our study the DSR experimental design was constrained to temperature scanning, neglecting frequency and time domain scanning, which precluded a comprehensive assessment of mid-temperature fatigue performance. As a result, the fatigue behavior at intermediate temperatures necessitates further research.